Extent Of Reformation Of Prison Inmates Using Prison Education Programmes In Anambra State - Adebola, Helen Ebunoluwa; Ogbaka, Luke Chidiebele; Ogbaka, Luke Chidiebele; Orji, Felicia Nwabundo; Orji, Felicia Nwabundo (Advances in Social Sciences Research Journal, 2018)
The study examined the extent of reformation of prison inmates in Anambra State using prison education programmes. Three research questions guided the study. Descriptive survey design was used for the study. The population of the study was made up of 500 instructors facilitating the education of prisoners in Anambra state. No sample was done because the population was manageable. Questionnaire was the instrument for data collection. The researchers administered 500 copies of the questionnaire to the respondents. Only 485 (97%) copies were completed and returned. Means was employed to answer the research questions. The findings of the study revealed that the instructors have not properly equipped prison inmates with the technical and vocational education to a fairly low extent. The findings of the study showed that the instructors have not properly equipped prison inmates to a fairly low extent with the reading and writing skills needed for acquiring information that can immediately be used for improving standards. The findings of the study further revealed that the instructors have not properly guided prison inmates to a fairly low extent with the basic knowledge and civic skills needed to become good citizens if released back into the society. Based on the findings, it was recommended among others that technical and vocational education skills should be adequately imparted to prison inmates by the Nigerian Prison Service and the Non-Governmental Organizations should foster their reformation, rehabilitation and reintegration.